Escalating Health Care Cost due to Unnecessary Diagnostic Testing - Chaudhary, Muhammad Azam Ishaque; Nisar, Asim (Mehran University Research Journal of Engineering and Technology, 2017)
Focusing on health care systems can improve health outcomes now and in the future. Growing economies have serious concerns on the rising cost of health, whereas, in under developed countries like Pakistan, it is not emphasized yet at all. The research is conducted to improve a unique aspect of health care systems to provide effective, patient-centred, high-standard health care while maintaining the cost effectiveness. Research is being qualified in two paradigms qualitative and quantitative. In qualitative research, expert’s interviews have been taken to get the basic knowledge of radiology based testing and their prerequisites, in quantitative research ordered are being analysed to check the frequency and if they are unnecessary or qualified medical necessity guidelines as established in qualitative method. Analysis was made on the basis of the trinity relationship of diagnosis, symptoms and respected order to determine the necessity of the order to get its impact on cost of the overall health of those patients and point out more than 50% unnecessary orders are being performed in two government hospitals. The situation is alarming and policy makers should focus on unnecessary ordering to avoid out of pocket expenses and improve quality of care. The research helps in successful application of health care system modifications and policies pertaining to one aspect of health systems, i.e. cost-effectiveness of health care.